IoT Untuk Inovasi Pembayaran Elektronik Di sekolah: Desain Dan Implementasi Prototipe Kartu E-Money Menggunakan NodeMcu 8266 - Puji Widianto, Teguh; Berlian Tri Cahyono, Bagas; Saputri, Nurbaiti; Nurrohman, Taufiq; Crisyanto, Hendy (Lembaga Pengembangan Kinerja Dosen, 2024)
The growth of the digital industry has brought about numerous transformations in the way people transact, especially through the use of e-money. The use of e-money in various countries such as China, America, and other developed nations has reached billions of dollars annually. Similarly, Indonesia is experiencing a surge in the use of QRIS, OVO, and DANA, transforming the way people pay. However, the current e-money technology is not yet applicable for financial transactions at the school level, specifically for junior high, elementary, and kindergarten schools, as the use of smartphones is not permitted at these levels. Therefore, it is proposed to use cards for payments. This research aims to design and implement a prototype of a payment system using e-money cards, utilizing NodeMCU ESP8266 technology and RFID RC522 modules. The research methodology employs the ADDIE model, which includes needs analysis, hardware and software design, and prototype implementation. The result is a developed system that can easily facilitate payments using e-money cards detected by the RFID reader and processed by NodeMCU. Transaction data is sent via Wi-Fi to the MySQL database. A web interface is created for user registration, balance top-ups, and transaction logs. The prototype works well and promises improvements for more advanced electronic payment systems in the future.